2010
DOI: 10.1097/nna.0b013e3181fc1
|View full text |Cite
|
Sign up to set email alerts
|

A Patient-Centered Model to Improve Metrics Without Cost Increase

Abstract: The need for patient-centeredness in care delivery has been articulated for decades, yet meaningful progress toward patient-centered healthcare has been hobbled by the lack of a replicable patient-centered care model and method. The authors describe the patient- and family-centered care method, built around viewing every care experience through the eyes of the patient and family, and its outcomes proving the approach is replicable and sustainable while improving outcomes without additional cost. A follow-up ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(16 citation statements)
references
References 5 publications
0
14
0
2
Order By: Relevance
“…This study has implications for health care policy makers as well. Research has shown that a patient-centered focus is also one of the strategies to achieving cost-effective quality of care 30. Pay for performance has been shown to have an impact on patient satisfaction by enhancing physician knowledge, increasing awareness of guidelines, encouraging prevention and follow-up, reducing errors and costs, ensuring a uniform level of care, and motivating physicians to deliver better care.…”
Section: Discussionmentioning
confidence: 99%
“…This study has implications for health care policy makers as well. Research has shown that a patient-centered focus is also one of the strategies to achieving cost-effective quality of care 30. Pay for performance has been shown to have an impact on patient satisfaction by enhancing physician knowledge, increasing awareness of guidelines, encouraging prevention and follow-up, reducing errors and costs, ensuring a uniform level of care, and motivating physicians to deliver better care.…”
Section: Discussionmentioning
confidence: 99%
“…Combining TDABC + PFCC M/P proved to be an effective means of identifying the major cost drivers, capacity utilization, areas of opportunity for improving efficiencies, and experiences for this patient population, and all of the information required to participate successfully in bundling and RBP programs for THR and TKR. While the PFCC M/P has already been shown to improve value in health care [4][5][6][7][8][9][10][11], knowing the major cost drivers over a full cycle of care and having the tools to drive down these costs while protecting outcomes and experiences provides the mechanism to further improve value in health care. We are now beginning to build teams to pilot and operationalize identified improvement opportunities.…”
Section: Resultsmentioning
confidence: 99%
“…Identifying the current state of a care experience through the PFCC M/P approach involves process mapping (which in PFCC terms is called Care Experience Flow Mapping) using a tool called Shadowing, which is the real-time observation of patients and families through each segment of their health care journey. The PFCC M/P has been found to improve all three components of value in health care -experience, outcomes, and costs [4][5][6][7][8][9][10][11] -what we call the PFCC Trifecta.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many of the improved outcomes based on these metrics have been published, including findings of decreased staff turnover and decreased costs (DiGioia et al, 2010;Meyer, 2011) in trauma services and improvements in process efficiency . Many of the improved outcomes based on these metrics have been published, including findings of decreased staff turnover and decreased costs (DiGioia et al, 2010;Meyer, 2011) in trauma services and improvements in process efficiency .…”
Section: Resultsmentioning
confidence: 99%